XRD and IR revelation of a unique g-C3N4 phase with effects on collagen/hydroxyapatite bone scaffold pore geometry and stiffness - Asimeng, BO; Karadag, I; Xu, Y; Iftekhar, S; Czernuszka, J (Springer, 2020)
Pore geometry (pore size and pore interconnectivity) and stiffness are important design requirements for 3D-scaffold fabrication. The required pore geometry allows the passage of growth factors for cell proliferation and removal of waste products, whereas the stiffness influences attachment of osteogenic cells. This work fabricates a 3D scaffold from collagen (Col) and snail shell hydroxyapatite (HApS) and examines the influence of the HApS on the scaffold pore geometry and stiffness. The scaffolds were fabricated using freeze-drying method. Col alone and Col-commercial hydroxyapatite (Col–HApC) scaffolds were used as controls. Scanning electron microscope (SEM) reveals well-interconnected pores for Col–HApS with a mean pore size of 246.9 ± 68.7 μm, which was statistically (p < 0.05) same as that of Col scaffolds 224.4 ± 85.7 μm and different (p < 0.05) from Col–HApC scaffolds 125.5 ± 26.7 μm. Mechanical testing showed a stiffness of 20.8 ± 0.4 kPa, 181.2 ± 11.8 kPa, and 206.9 ± 14.1 kPa for Col, Col-HApC, and Col–HApS, respectively. Uniquely, X-ray diffractometry (XRD) and Infrared (IR) spectroscopy of Col–HApS revealed phases and functional groups that were comparable to graphitic-like carbon nitride (g-C3N4) polymeric structure. It was found that the structural change was responsible for the well-interconnected large pores and high stiffness of the scaffold. It is expected that the effect brings a wide range of functions (such as better cell attachment and nutrient transport) in the scaffold for osteogenesis. The findings indicate that Col–HApS scaffolds would promote osteogenic cell response more usefully than Col–HApC or Col scaffolds.